1980
DOI: 10.3109/00016348009154627
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Three Methods for External Fetal Cardiography

Abstract: Phonocardiography, abdominal electrocardiography and ultrasound cardiography are the three methods for external fetal cardiography. In the present study the methods have been compared regarding the quality of the graphs. The patients (163) were between the 34th and the 40th week of gestation. Graphs with less than 15 per cent failure or artifacts were found in 23.4 per cent for phonocardiography, 55.2 per cent for abdominal electrocardiography and 85.9 per cent for ultrasound cardiography. It could be shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Doppler ultrasound technology is widely used for FHR monitoring, although its potential problems of reliability, accuracy, influence by fetal or maternal movement, and insertion of the MHR are recognized. The use of afECG‐based FHR monitoring was proposed several decades ago (10,11) but its use was compromised by a limited ability to extract the fetal signal reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasound technology is widely used for FHR monitoring, although its potential problems of reliability, accuracy, influence by fetal or maternal movement, and insertion of the MHR are recognized. The use of afECG‐based FHR monitoring was proposed several decades ago (10,11) but its use was compromised by a limited ability to extract the fetal signal reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the present study, which was conducted on a 5-fold larger research group (144 vs. 773) this correlation was not demonstrated (r -0.005; CI 0.079-0.069; p > 0.892). In the case of intrapartum electrocardiography, Solum et al showed an inverse relationship between patient's BMI and the quality of the fECG signal [27].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity affects to a minor degree the quality of external cardiotocographic registration [123]. Nonreactive nonstress tests were not more frequently observed and showed no false negative results in obese patients [124].…”
Section: Foetal Surveillancementioning
confidence: 99%